PENGARUH KARAKTERISTIK PERSONAL AUDITOR TERHADAP TINGKAT PENERIMAAN PENYIMPANGAN PERILAKU DALAM AUDIT DAN KUALITAS HASIL AUDIT - Pertiwi, Dian; Azlina, Nur (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study was conducted to examine the relationship of personal characteristicswith the level of acceptance of deviant behavior and its effect on quality auditresulting audit. Personal characteristics of auditors consists of locus of control,emotional quotient and performance auditors. The object under study is BPKPRepresentative in Pekanbaru City Riau Province. Data analysis method used in thisresearch is the method of path analysis is done with the help of software SmartPLS.Collecting data using secondary data and primary data obtained through thequestionnaire of the respondents research. The result showed that 1) Locus ofcontrol affects the level of acceptance of deviant behavior in the audit. 2) EmotionalQuotient affect the level of acceptance of deviant behavior in the audit. 3) Theperformance auditor did not significantly influence the acceptance of deviantbehavior in the audit. 4) Locus Of Control directly influence the audit quality. 5)Emotional Quotient direct effect on audit quality. 6) Performance auditors directlyinfluence the audit quality. 7) Locus of control effect on audit quality, moderatedacceptance of deviant behavior in the audit. 8) Emotional Quotient has no effect onaudit quality, moderated acceptance of deviant behavior in the audit. 9) Theperformance auditor has no effect on audit quality, moderated acceptance of deviantbehavior in the audit. 10) The acceptance of deviant behavior in the audit effect onaudit quality.Keywords: Quality audit, locus of control, emotional quotient, performance auditor,audit behavioral deviations acceptance (dysfungsional audit)